A halogen- and hydrogen-bonding [2]catenane for anion recognition and sensing1. Issue 12 (11th February 2015) - Mercurio, James M.; Caballero, Antonio; Cookson, James; Beer, Paul D.
<x xml:space="preserve">Abstract</x> A mixed halogen- and hydrogen-bonding hetero-[2]catenane has been synthesised via anion templation and demonstrated to bind and sense oxoanions.